GE_GERICHTE P/15066/2022 vom 5. November 2025 - GE Cour de justice (2025)
PARTIE À LA PROCÉDURE;PLAIGNANT;LÉSÉ;DOMMAGE CAUSÉ À UN TIERS;ESCROQUERIE;ABUS DE CONFIANCE | CPP.115; CPP.118; CP.146; CP.138